Calibration of rotation axes for multi‐axis goniometers in macromolecular crystallography. Issue 5 (13th September 2018) - White, K. Ian; Bugris, Valeria; McCarthy, Andrew A.; Ravelli, Raimond B. G.; Csankó, Krisztián; Cassetta, Alberto; Brockhauser, Sandor
Abstract : An easy to perform rotation calibration procedure has been developed for miniKappa and/or other multi‐axis goniometers used in macromolecular crystallography to enhance the precision of experiments involving crystal reorientations. Abstract : The installation of multi‐axis goniometers such as the ESRF/EMBL miniKappa goniometer system has allowed the increased use of sample reorientation in macromolecular crystallography. Old and newly appearing data collection methods require precision and accuracy in crystal reorientation. The proper use of such multi‐axis systems has necessitated the development of rapid and easy to perform methods for establishing and evaluating device calibration. A new diffraction‐based method meeting these criteria has been developed for the calibration of the motors responsible for rotational motion. This method takes advantage of crystal symmetry by comparing the orientations of a sample rotated about a given axis and checking that the magnitude of the real rotation fits the calculated angle between these two orientations. Hence, the accuracy and precision of rotational motion can be assessed. This rotation calibration procedure has been performed on several beamlines at the ESRF and other synchrotrons. Some resulting data are presented here for reference.